2020
DOI: 10.1038/s41416-020-0790-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on cervical cancer risk stratification by cytology and HPV genotype to inform the management of HPV-positive women in routine cervical screening

Abstract: BACKGROUND: HPV16/18 detection may improve cervical cancer risk stratification and better guide which HPV-positive women warrant immediate colposcopy/biopsy. We estimated risks of cervical precancer and cancer by HPV genotype and cytology during the implementation phase of primary HPV testing in Norway. METHODS: A total of 3111 women, aged 34-69 years, testing HPV-positive at baseline and undergoing cytology testing from February 2015 to April 2018 had data available for analysis. Risk estimates with 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 57 publications
8
44
0
1
Order By: Relevance
“…Although one study reported that the prevalence rate of HR-HPV among women with ASC-US was 41.7%, 23 another study reported a prevalence rate of 23%. 24 The prevalence rate of HR-HPV among patients with ASC-US was 47.6% in our research. Moreover, among patients with ASC-US whose biopsies proved to be CIN2+, the infection rates of HPV16, HPV18, HPV31, HPV33, HPV52 and HPV58 were 47.9%, 7.0%, 5.4%, 5.8%, 18.6% and 21.1%, respectively.…”
Section: Discussionsupporting
confidence: 44%
“…Although one study reported that the prevalence rate of HR-HPV among women with ASC-US was 41.7%, 23 another study reported a prevalence rate of 23%. 24 The prevalence rate of HR-HPV among patients with ASC-US was 47.6% in our research. Moreover, among patients with ASC-US whose biopsies proved to be CIN2+, the infection rates of HPV16, HPV18, HPV31, HPV33, HPV52 and HPV58 were 47.9%, 7.0%, 5.4%, 5.8%, 18.6% and 21.1%, respectively.…”
Section: Discussionsupporting
confidence: 44%
“…Thus, the HPV types detected in screening considerably affect the harms and benefit balance of the entire program, an observation, which was supported by a recent study confirming clinical benefit of immediate colposcopy referral for all HPV16/18-positive women whereas women with other hrHPV infections are triaged with cytology in a pre-vaccinated population. 41 One should notice that in Asian countries, for example, HPV58 has been reported to have a far more oncogenic profile compared with the Nordic countries, 42,43 implying that regional/ geographical differences should be considered in establishing an optimal screening program. Now, the optimal screening scenario should be considered for the scenario when all 2 v and 4 v HPV vaccine-targeted HPV types are eliminated, with an assumed prevalence of carcinogenic HPVs reduced to 28% among those who enter the screening program.…”
Section: Discussionmentioning
confidence: 99%
“…The same conclusion was reached by a recent data study on the implementation phase of the hrHPV-based screening programme in Norway, where CIN3+ risk was estimated for cytology results and HPV genotypes. By inviting women with HPV-OHR and low-grade cytology for a repeat test instead of referring these women for colposcopy, the harms and benefits of the screening programme were found to be more balanced [27].…”
Section: Discussionmentioning
confidence: 99%